Transforming E-governance: the potential of blockchain in the public sector - Nuryanti, Linda; Ayuningtyas, Fara; W. Sumunaringrum, Monica D.; Ruswendi, Wenwen; Srimoeljanto, Agoeng; Sutejo, Agus; Susanto, Triyono; Nurmayni, Ratna (Indonesian Journal of Electrical Engineering and Computer Science, 2025)
Blockchain technology has become a transformative innovation in the digital governance landscape, offering new opportunities to enhance transparency, accountability, and citizen trust. This study offers an extensive bibliometric and thematic examination of international research on blockchain in E-governance from 2019 to 2024. Using data from the Scopus database, the analysis examines publication trends, leading countries, collaboration networks, and the intellectual structure of the field. The findings reveal that research output has grown steadily, dominated by technologically advanced nations such as China, India, and the United Kingdom. The thematic mapping identifies core clusters, including transparency, E-government, and public sector innovation, alongside emerging themes such as artificial intelligence (AI) integration, smart cities, and digital transformation. By integrating bibliometric and thematic analyses, this study offers a comprehensive understanding of how blockchain research evolves within public governance. Despite significant progress, challenges remain, particularly regarding empirical validation, governance frameworks, and regional disparities in adoption. Future research should explore a more complex roadmap for blockchain implementation in government through three interrelated dimensions: technical development, policy and regulatory frameworks, and socio-institutional adaptation. This multidimensional perspective underscores blockchain’s capacity to support secure, inclusive, and data-driven forms of digital governance.